2021
DOI: 10.1002/sdtp.14950
|View full text |Cite
|
Sign up to set email alerts
|

P‐109: Stress‐Free Folding Hinge for Foldable OLED Display Device

Abstract: The core technologies for the foldable display device are a flexible OLED panel, a flexible cover window and a folding hinge. Among them a hinge controls folding motion trajectory of an OLED panel. It is very important for an OLED panel not to apply any additional stress during folding motion. We developed the stress‐free folding (SFF) hinge with a virtual axis structure (VAS). Using SFF hinge we can achieved that the stress on OLED panel during folding is almost same as the free folding stress. As a result, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Moreover in 2020, Zhang et al 27 designed a 17.3-inch WQHD foldable AMOLED display. Additionally, in 2021, Han et al 28 demonstrated a SFF (stress-free folding) hinge with VAS (virtual axis structure) and MAS (modulized assembly structure). The proposed hinge provided stress-free folding motion and 200k folding reliability having less than 20% torque reduction.…”
Section: Classification Of Oledmentioning
confidence: 99%
“…Moreover in 2020, Zhang et al 27 designed a 17.3-inch WQHD foldable AMOLED display. Additionally, in 2021, Han et al 28 demonstrated a SFF (stress-free folding) hinge with VAS (virtual axis structure) and MAS (modulized assembly structure). The proposed hinge provided stress-free folding motion and 200k folding reliability having less than 20% torque reduction.…”
Section: Classification Of Oledmentioning
confidence: 99%
“…The centers of these half circle slides are located above top of plates which an OLED panel is attached on, inside of OLED panel when it attached on the plates in order to minimize the stress by folding motion. [5] In general, its torque value is controlled by the spring force and CAM shape on one side of the spring as shown in figure 2. When hinge folds, rotating part and stationary part are rubbed each other and spring force add friction force on it.…”
Section: Sff Hinge With Vasmentioning
confidence: 99%
“…At the SID 2021 last year, we have presented our stress-free folding (SFF) hinge technology with the virtual axis structure (VAS). [5] We would enlarge this technology to large size foldable device and then it can have the same folding radius as foldable mobile phone, ~ 1.5mm. In order to apply this SFF hinge up to 17" size, it has to have very high torque value to have freestop function.…”
Section: Introductionmentioning
confidence: 99%
“…The flexible electronic device industry has experienced tremendous growth since the introduction of foldable smartphones in late 2018 [1,2]. Despite their popularity, the market for flexible devices is still in its early stages and limited to high-end products due largely to the complex design and manufacturing challenges.…”
Section: Introductionmentioning
confidence: 99%